Viewpoints of the target population regarding barriers and facilitators of colorectal cancer screening in the Czech Republic - Kroupa, Radek; Ondrackova, Monika; Kovalcikova, Petra; Dastych, Milan; Pavlik, Tomas; Kunovsky, Lumir; Dolina, Jiri (World journal of gastroenterology, 2019)
BACKGROUND: Public awareness of colorectal cancer (CRC) and uptake of CRC screening remain challenges. The viewpoints of the target population (asymptomatic individuals older than 50) regarding CRC screening information sources and the reasons for and against participation in CRC screening are not well known in the Czech Republic. This study aimed to acquire independent opinions from the target population independently on the health system. AIM: To investigate the viewpoints of the target population regarding the source of information for and barriers and facilitators of CRC screening. METHODS: A survey among relatives (aged 50 and older) of university students was conducted. Participants answered a questionnaire about sources of awareness regarding CRC screening, reasons for and against participation, and suggestions for improvements in CRC screening. The effect of certain variables on participation in CRC screening was analyzed. RESULTS: Of 498 participants, 478 (96%) respondents had some information about CRC screening and 375 (75.3%) had participated in a CRC screening test. General practitioners (GPs) (n = 319, 64.1%) and traditional media (n = 166, 33.3%) were the most common information sources regarding CRC screening. A lack of interest or time and a fear of colonoscopy or positive results were reported as reasons for non-participation. Individuals aged > 60 years [adjusted odds ratio (aOR) = 2.30, 95% confidence interval (CI) (1.42-3.71), P = 0.001], females (aOR = 1.95, 95%CI (1.26-3.01) P = 0.003), and relatives of CRC patients (aOR = 4.17, 95%CI (1.82-9.58) P = 0.001) were more likely to participate in screening. Information regarding screening provided by physicians - GPs: (aOR = 8.11, 95%CI (4.90-13.41), P < 0.001) and other specialists (aOR = 4.19, 95%CI (1.87-9.38), P = 0.001) increased participation in screening. Respondents suggested that providing better explanations regarding screening procedures and equipment for stool capturing could improve CRC screening uptake. CONCLUSION: GPs and other specialists play crucial roles in the successful uptake of CRC screening. Reduction of the fear of colonoscopy and simple equipment for stool sampling might assist in improving the uptake of CRC screening.
Keywords: senioři; Colonoscopy; Male; Female; Colorectal Neoplasms; Aged; Middle Aged; kolonoskopie; Occult Blood; plošný screening; věkové faktory; Česká republika; Mass Screening; průřezové studie; adherence pacienta; Early Detection of Cancer; Health Knowledge, Attitudes, Practice; mužské pohlaví; ženské pohlaví; kolorektální nádory; Age Factors; Patient Compliance; Surveys and Questionnaires; Czech Republic; časná detekce nádoru; průzkumy a dotazníky; senioři nad 80 let; Cross-Sectional Studies; lidé středního věku; Fear; okultní krev; Aged, 80 and over; lidé; Humans; zdraví - znalosti, postoje, praxe; strach